Expert Validation of the Green Competencies Model: Strengthening Sustainable Vocational Education - Latif, Muh Abdul; Widiaty, Isma; Abdullah, Ade Gafar (Universitas Ahmad Dahlan, 2025)
The development of a green competencies-based model is an urgent need in supporting the integration of Education for Sustainable Development (ESD) into the vocational education curriculum. This research aims to validate the green competencies model through expert validation, to ensure its feasibility and relevance in supporting the vocational education curriculum. Forum Group Discussion (FGD) was adopted as this study tests the feasibility of the model. Content Validity Index (CVI) was used to analyze the expert feedback of each question. The results showed that the green competencies model plays a significant role in improving environmental awareness, technical skills, and sustainability values among the workforce and learners. The model received its feasibility value (1>0.83) and has been improved to perfect its construction elements as feedback for each criticism and suggestion, so it is ready to be used as a recommendation to be integrated in the vocational education curriculum. The development of this model is expected to be a guideline for vocational education institutions in developing ESD-based curriculum, as well as supporting the readiness of graduates to contribute to the green economy and create a sustainable future.